(untitled) (Journal of Partial Differential Equations, 2014)
In this paper, we study a class of reaction-diffusion systemswith Beddington-DeAngelis function response. The global asymptotic convergence is established by using the comparison principle and the method of monotone iterations, which is via successive improvement of upper-lower solutions function.